Uses and perfomance of the IUCN susytem of management categories for protected areas. Speaking a common language / Bishop Kevin, Nigel Dudley, Adrián Phillips - Bishop, Kevin (Suiza: The world Conservation Unión, 2004)
The apeaking a common language Project, the emergence of an international system of protected area management categories; evaluating the original purposes of the IUCN categories, encouraging national proted area systems; evaluating the new uses made of the IUCN categories, providing a basis for legislation; using the IUCN categories more effectively the definition and purposes the categories dissemination of information; conclusions and recommendations
Content, illustrated, table, graph, map
Col. Agro
Keywords: 1.CONSERVATION-PROTECTION 2. COMMON LANGUAGE 3. ECOLOGY 4. AGROFORESTRY